2019
DOI: 10.1590/1806-3713/e20170451
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a rapid molecular test for tuberculosis in sputum samples, bronchoalveolar lavage fluid, and tracheal aspirate obtained from patients with suspected pulmonary tuberculosis at a tertiary referral hospital

Abstract: Tuberculosis continues to be a major public health problem worldwide. The aim of the present study was to evaluate the accuracy of the Xpert MTB/RIF rapid molecular test for tuberculosis, using pulmonary samples obtained from patients treated at the Júlia Kubitschek Hospital, which is operated by the Hospital Foundation of the State of Minas Gerais, in the city of Belo Horizonte, Brazil. This was a retrospective study comparing the Xpert MTB/RIF test results with those of standard culture for Mycobacterium tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Some studies have concluded that Xpert detects MTB for up to five years after treatment [48,49]. Therefore, in these cases, the diagnosis of active TB should be performed by smear and culture tests, whereas the molecular test is recommended for early diagnosis and is not indicated for monitoring therapeutic response [50]. In our study, there were five patients who did not have active TB but had previously undergone treatment, and one patient was under treatment at the time of the molecular test and were considered "not TB".…”
Section: Plos Onementioning
confidence: 99%
“…Some studies have concluded that Xpert detects MTB for up to five years after treatment [48,49]. Therefore, in these cases, the diagnosis of active TB should be performed by smear and culture tests, whereas the molecular test is recommended for early diagnosis and is not indicated for monitoring therapeutic response [50]. In our study, there were five patients who did not have active TB but had previously undergone treatment, and one patient was under treatment at the time of the molecular test and were considered "not TB".…”
Section: Plos Onementioning
confidence: 99%
“…Bronchoscopy can be valuable for these patients as it can obtain suitable specimens from the lower respiratory tract while inspecting all the available airways (Mondoni et al, 2017). Literature regarding the diagnostic accuracy of the Xpert assay on bronchoalveolar lavage fluid (BALF) is limited, and most studies have used small sample sizes (Barnard et al, 2015;Fakey Khan et al, 2019;Kilaru et al, 2019;Li et al, 2020;Lu et al, 2018;Pan et al, 2018;Silva et al, 2019;Theron et al, 2013;Theron et al, 2014). Due to this limited research, no formal recommendation for using the Xpert MTB/RIF assay on BAFL exists.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 50 articles: 17 [7,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] in the adult BAL group, 14 [35,[40][41][42][43][44][45][46][47][48][49][50][51][52] in the adult ES group, 7 [35,45,50,[53][54][55][56] in the adult IS group, 2 [57,58] in the pediatric ES group, 6 [57,[59][60][61][62][63] in the pediatric GA group, and 9 [59,[64][65][66][67]…”
Section: Studies' Characteristicsmentioning
confidence: 99%